Ayat-Ayat Eskatologi: Perspektif Epistimologi dari al-Zamakhsyari - Naffasa, Resya Farasy Fitrah; Ilhamni, Ilhamni; Faizin, Faizin (Jurnal Ulunnuha, 2024)
This article aims to examine the perspective of al-Zamakhsyari, as a classical interpreter whose book of interpretation is referred to as the main book of interpretation of the lughowi style, related to the eschatological verses in the surah al-Zalzalah to prove the epistemological construction of interpretation based on the source, method and validity of interpretation. The object of this research is the text and its relationship to past events, so a literature study was conducted to study the content analysis using a historical approach. The primary data in this study is the book Tafsir al-Kasysyaf and is supported by literature on the epistemology of interpretation in a philosophical approach. The results of the study reveal that al-Zamakhsyari has interpreted the surah al-Zalzalah by referring to Arabic grammar, poems and the hadith of the prophet. In the epistemology of interpretation, verses about eschatology are not sufficient if interpreted linguistically separately, although it has proven the validity of the coherence of interpretation, but he remains consistent in using this method, even in line with the interpretation of zilzal which is a description of the state of the earth when it shakes according to the reality and scientific facts about earthquakes, and in line with the evidence about the apocalypse which will definitely happen as the terminology in the Qur'an